Microporous fluorine-containing polyimide film material and preparation method thereof
By using specific graft groups in the polyamic acid system to promote phase separation, the problem of difficult control of pore size and pore distribution of pores of pores and pore distribution of pores are solved, and the preparation of a multi-porous fluoro-containing polyimide film with high mechanical properties and heat resistance is achieved, which is suitable for electronic products with high frequency and high-speed signal transmission.
Patent Information
- Application Number
- CN202510067838.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The prior art is difficult to effectively control the pore size and pore distribution of porous polyimide films, and there are many preparation processes, resulting in poor mechanical performance and low production efficiency, making it difficult to achieve large-scale production.
By selecting C2-C60 alkanoate alkyl groups and poly(dimethylsiloxane) groups as graft groups, the phase separation of the polyamic acid system is promoted, thereby forming uniform intrinsic micropores in the multi-porous fluoroporous polyimide film.
The preparation of a multi-porous fluoroporous polyimide film material with uniform pore size and pores is achieved, with high mechanical properties and heat resistance, and is suitable for electronic products with high frequency and high speed signal transmission.
Smart Images

Figure BDA0005244778470000041 
Figure BDA0005244778470000042 
Figure BDA0005244778470000061
Abstract
Description
Technical Field
[0001] The invention relates to the field of polyimide materials, in particular to a multi-microporous fluorine-containing polyimide film material and a preparation method thereof. Background Art
[0002] Polyimide film is an insulating material that can be used in integrated circuits. As an insulating material in integrated circuits, the quality of its mechanical properties, thermal stability, dielectric properties and hygroscopic properties directly determines the efficiency of electronic signal transmission and the service life of the device. In terms of heat resistance, polyimide materials are different from other polymer materials in that they have phthalimide rings on the molecular chain. In addition, polyimides with different structures also have considerable differences in various properties. Ordinary structure polyimides have been widely studied. It has become a consensus in the research of polyimide materials that certain properties will be improved by introducing special groups into the molecular structure of ordinary polyimide.
[0003] Fluorine is the smallest atom except hydrogen. Fluorine has always appeared in a very magical appearance. As a highly active element, fluorine plays a huge role in many fields such as medicine and refrigeration. For example, polymers represented by polytetrafluoroethylene have become very important materials in the field of industrial technology. As early as the 1960s, fluorine was introduced into the polyimide structure to obtain fluorine-containing polyimide materials. The main chain of the fluorine-containing polyimide material is a fluorine-containing structure, and the fluorine structure includes hydrogen on the aromatic ring, heterocycle or aliphatic chain replaced by fluorine or fluoroalkyl. Fluorine-containing polyimide is divided into the following categories according to the structure of the fluorine substituent and the substitution position in the polymer: a. Polyimide with a perfluorinated aliphatic chain as the main chain; b. Polyimide containing trifluoromethyl and hexafluoropropyl; c. Polyimide with hydrogen on the aromatic ring replaced by fluorine; d. Polyimide containing fluorinated aliphatic side chains; e. Perfluorinated polyimide.
[0004] Fluorine is the element with the highest electronegativity among all elements. The generated CF bond energy is very high and difficult to be broken. The characteristics reflected in the material are that the thermal stability of fluorinated polyimide is improved, the color is light and the light transmittance is better. In addition, fluorinated polyimide has a lower dielectric constant, water absorption and high solubility. In particular, low dielectric constant and low water absorption are the most important performance indicators of insulating materials for chip electronic products on the basis of good heat resistance. Lower dielectric constant can ensure faster signal transmission, and low water absorption ensures that electronic products have better environmental adaptability. The light transmittance of fluorinated polyimide film will have greater competitive advantages in photovoltaic power generation and flexible display.
[0005] With the gradual acceleration of the process of informatization, the integration of electronic products is getting higher and higher. Even the dielectric properties of materials such as fluorinated polyimide cannot meet the requirements of high-speed and high-frequency signal transmission. In nature, the dielectric constant of air is the lowest, about 1.0. If tiny micropores are formed inside the polyimide film, a two-phase system of polyimide-air is formed, which can greatly reduce the dielectric constant and dielectric loss of the material. Among the polyimide products with many structures, dense fluorinated polyimide films have been used in integrated circuits, which improves the transmission speed and stability of electronic signals. If a microporous structure can be formed inside the fluorinated polyimide film, the dielectric constant and dielectric loss of the material will be further reduced, greatly improving the high-speed and high-frequency transmission of electronic signals. Fluorinated polyimide film will become the temperature-resistant material with the best dielectric properties. Guided by the idea of creating pores inside the film to reduce the dielectric constant, how to prepare fluorinated polyimide films with microporous structures has become a research and development hotspot in recent years.
[0006] Due to the unique structure and characteristics of polyimide, it is difficult to form natural micropores inside the film. Most methods promote the formation of pores or hard-made pores through external processes. In most cases, these methods obtain microporous structures at the expense of some of the intrinsic properties of polyimide. The methods that have been disclosed are divided into the following: etching method, phase conversion method, and electrospinning method. Some of these methods cause irreversible degradation of the film by external processes, such as etching method and phase conversion method. The etching method requires the use of strong acid to pickle and etch away the inorganic substances doped inside the film after film formation. On the one hand, this process cannot guarantee that there is no residue inside, and on the other hand, it will affect the mechanical properties of the film. The phase conversion method is to promote the phase separation of the system from the outside through the intervention of a poor solvent in the semi-dry film stage. The channel where the original solvent is leached forms pores. The difficulty of the poor solvent to enter the interior of the semi-dry film will inevitably lead to differences in the phase separation between the inside and outside of the film. This can be confirmed by the fact that most of the pores are formed on the outside of the film and have poor uniformity. In addition, the short-term promotion of phase separation by the addition of an external solvent will also affect the regularity of the molecular structure, thereby affecting the mechanical properties. Electrospinning is a common method for achieving through holes on both sides of the film. It generates polyamide acid filaments through electrostatic action and forms a porous film through stacking. The pore size formed by this method is relatively large and the mechanical properties are poor. While the above methods have their own shortcomings, the biggest problem is that they are difficult to mass produce due to the numerous steps or discontinuous film making process.
[0007] It can be seen that the pore size and pore distribution of the porous polyimide film prepared by the existing technology cannot be effectively controlled. Some of the processes used may cause film degradation, resulting in poor mechanical properties of the film. The involvement of multiple processes leads to low production efficiency and difficulty in large-scale production, resulting in inherent technical difficulties in forming tiny pores inside the fluorinated polyimide film.
[0008] In addition, while the introduction of fluorine structure into polyimide brings many excellent properties, there are also certain problems. First, the formation of uniform intrinsic micropores in the polyimide film requires significant phase separation of the system in the imidization stage of the film preparation process. At this time, the compounds released by the cyclization reaction remain in the system. When the temperature rises to the point where the released compounds evaporate and escape, the gaps occupied by them remain to form a microporous structure. The introduction of fluorine structure improves the solubility of polyimide, and the improvement in solubility is not conducive to the occurrence of phase separation in the system. Second, because the fluorine element has a very strong electron-withdrawing effect, it reduces the reactivity of its adjacent functional groups, which is not conducive to the molecular chain growth of the polymer. If other chemical structures are grafted on the monomer before the polymerization reaction, the reactivity of the polymerizable functional groups on the fluorine-containing monomer will be further reduced, which will have a great impact on the mechanical properties. Summary of the invention
[0009] In view of this, the technical problem to be solved by the present invention is to provide a microporous fluorinated polyimide film material and a preparation method thereof. The preparation method provided by the present invention can obtain a microporous fluorinated polyimide film material with uniform pore size and porosity, and has high mechanical properties and heat resistance.
[0010] The present invention provides a microporous fluorine-containing polyimide film material, which is obtained by reacting a fluorine-containing polyamide ester having a structure of formula I with polyimide;
[0011]
[0012] Wherein, said z≥1000;
[0013] Ar1 and Ar2 are independently selected from substituted or unsubstituted fluorine-containing aromatic groups, substituted or unsubstituted fluorine-containing heteroaromatic groups, substituted or unsubstituted fluorine-containing aliphatic groups, substituted or unsubstituted aromatic groups, substituted or unsubstituted heteroaromatic groups, substituted or unsubstituted aliphatic groups;
[0014] The M1 and M2 are independently selected from C2 to C 60 Alkanoate alkyl or poly (dimethylsiloxane) group, and the M1 and M2 are the same or different;
[0015] The structural unit of the fluorine-containing polyamide ester includes at least one fluorine-containing structural unit of Ar1 and Ar2 and a structural unit in which both Ar1 and Ar2 are free of fluorine.
[0016] The structural unit of the fluorinated polyamide ester of the present invention has side chain groups M1 and M2, wherein M1 and M2 are independently selected from C2 to C 60 Alkane ester alkyl or poly (dimethylsiloxane) group, and the M1 and M2 are the same or different; wherein the C2 to C 60 The alkanoate alkyl group is preferably C4 to C15 The alkanoate alkyl group may be a straight chain group or a branched chain group. Preferably, M1 and M2 are independently selected from C2 to C 60 Alkanoate alkyl or poly(dimethylsiloxane) group having the structure of Formula Ib;
[0017]
[0018] Wherein, n≥1, m≥1
[0019] The x is ≥ 1, preferably 5 to 15;
[0020] The R is a fatty chain.
[0021] The fluorinated polyamide ester having the structure of formula I of the present invention has a poly(dimethylsiloxane) group, that is, the structural unit of the fluorinated polyamide ester includes M1 and M2 both selected from C2 to C 60 The structural unit of alkanoate alkyl and at least one of M1 and M2 is a structural unit selected from poly(dimethylsiloxane) groups. The molar amount of the poly(dimethylsiloxane) group accounts for 5% to 30% of the total molar amount of M1 and M2, preferably 9% to 13%. 60 Alkane ester alkyl and poly (dimethylsiloxane) groups are used as grafting groups. After the groups are detached, they can effectively promote the phase separation of the system as poor solvents in the system, and the boiling point is suitable, and finally uniform intrinsic micropores are formed in the microporous fluorinated polyimide film. In addition, the pore size, distribution and porosity can be effectively controlled by the distribution ratio of the pore-forming groups on the molecular chain of the polymer intermediate.
[0022] The microporous fluorine-containing polyimide film material of the present invention includes fluorine-containing aliphatic polyimide materials and fluorine-containing aromatic polyimide materials and copolymerized polyimides thereof as well as block and graft copolymers. Specifically, the Ar1 and Ar2 in the fluorine-containing polyamide ester of the present invention are independently selected from substituted or unsubstituted fluorine-containing aromatic groups, substituted or unsubstituted fluorine-containing heteroaromatic groups, substituted or unsubstituted fluorine-containing aliphatic groups, substituted or unsubstituted aromatic groups, substituted or unsubstituted heteroaromatic groups, substituted or unsubstituted aliphatic groups. The structural unit of the fluorine-containing polyamide ester of the present invention includes at least one fluorine-containing structural unit in Ar1 and Ar2 and both Ar1 and Ar2 are fluorine-free structural units, and the molar proportion of at least one fluorine-containing structural unit in Ar1 and Ar2 to all structural units is preferably 1% to 100%. By controlling the proportion of fluorine-containing units, the comprehensive properties of the porous polyimide film skeleton body, such as heat resistance, water absorption, dielectric and mechanical properties, can be systematically regulated.
[0023] In order to improve the heat resistance of the obtained microporous fluorinated polyimide film material, the main chain of the fluorinated polyamide ester is preferably an aromatic structure. Preferably, Ar1 has one or more structures of formula Ar1-a to formula Ar1-i;
[0024]
[0025] Ar2 has one or more structures of formula Ar2-a to formula Ar2-h;
[0026]
[0027] Wherein, R1 and R2 are independently selected from H, F or trifluoromethyl;
[0028] The R 1 and R 2 One independently selected from the groups represented by the structures of Formula 1 to Formula 9;
[0029]
[0030] The X is selected from hydrogen, alkyl, cycloalkyl, aryl, fluoroalkyl, hydroxyl, alkoxy, phenoxy, cyano, nitro, amino, acetamido, ester, acyl, halide or carboxyl, preferably selected from -H, -Br, -Cl, -F, -NO2, -CN, -H, -CH3, -CH2CH3, -CH2CH2CH3, isopropyl, isobutyl, tert-butyl, cyclopentyl, cyclohexyl, phenyl or naphthyl.
[0031] The y is independently an integer of 1-4.
[0032] In the above formula Ar1-a to Ar1-i, the structure represented by formula Ar1-a is preferably The structure shown in formula Ar1-b is preferably The structure shown in formula Ar1-c is preferably or The structure shown in formula Ar1-d is preferably The structure shown in formula Ar1-e is preferably The structure shown in formula Ar1-f is preferably The structure shown in formula Ar1-g is preferably The R 1 Same as above, no further elaboration.
[0033] The microporous fluorinated polyimide film material provided by the present invention has a structure of Formula II;
[0034]
[0035] Wherein, Ar1, Ar2 and z are the same as those described in the above formula I and are not repeated herein.
[0036] The present invention also provides a method for preparing a microporous fluorinated polyimide film material as described in any of the above technical solutions, comprising the following steps: subjecting a fluorinated polyamide ester to an imidization reaction to obtain a microporous fluorinated polyimide film material. The fluorinated polyamide ester described in the present invention is the same as that described above and will not be described in detail. The reaction formula of the method for preparing a microporous fluorinated polyimide film material provided by the present invention is as follows:
[0037]
[0038] The temperature of the imidization reaction of the present invention is 50°C to 400°C, preferably 80°C to 350°C, and the time of the imidization reaction is 0.3h to 30h. The present invention can achieve the imidization of the fluorinated polyamide ester and the microporous nature of the obtained fluorinated polyimide film by heat treatment within the above temperature range. The imidization degree of the formed intrinsic microporous polyimide film material is usually above 90%, and most preferably 100%. The present invention adopts the thermal imidization known in the industry to prepare the microporous fluorinated polyimide film material. The film preparation process is continuous and efficient, and no other steps are required to avoid deterioration of the film. The continuity of the film preparation process can greatly reduce costs and realize the large-scale production of microporous fluorinated polyimide film materials.
[0039] Specifically, the present invention sequentially subjects the fluorinated polyamide ester glue to a pre-baking and curing stage, an imidization stage and a high-temperature treatment stage to obtain a microporous fluorinated polyimide film material; the present invention uses a step-by-step heating method for the fluorinated polyamide ester, which is more conducive to the preparation of a film with excellent comprehensive performance. Among them, the pre-baking and curing stage is also called a solvent volatilization stage, the temperature of the pre-baking and curing stage is 50°C to 150°C, preferably 80°C to 120°C, and the time of the pre-baking and curing stage is 0.1h to 10.0h. The present invention first subjects the fluorinated polyamide ester to the pre-baking and curing stage to volatilize the solvent of the fluorinated polyamide ester to obtain a film material, and the obtained film material is a semi-dry film, which still contains residual solvent, and preferably the mass fraction of the residual solvent accounts for 20 to 50% of the total mass of the semi-dry film. The imidization stage treatment of the present invention is also called the cyclization branch shedding stage treatment, and the temperature of the imidization stage treatment is 100°C to 250°C, preferably 120°C to 180°C, and the time of the imidization stage treatment is 0.1h to 10.0h. The high-temperature treatment stage treatment of the present invention is also called the pore formation stage treatment, and the temperature of the high-temperature treatment stage treatment is 180°C to 400°C, preferably 180°C to 350°C, and the time of the high-temperature treatment stage treatment is 0.1h to 10.0h. The chemical and physical changes in the above three stages will overlap, and for the sake of clarity, they are named after the main physical and chemical changes in this stage. In addition to the above-mentioned segmented heating method, a gradient heating method can also be used for imidization, and the preferred heating rate is 0.1°C / min to 5°C / min.
[0040] In some embodiments of the present invention, the fluorinated polyamide ester glue is coated on a carrier, and a pre-baking curing stage, an imidization stage and a high temperature treatment stage are sequentially performed to obtain a multi-microporous fluorinated polyimide film material. The fluorinated polyamide ester glue can be coated on a carrier using glue coating equipment known in the art, and the coating method can be slit-type scraping, baffle-type scraping, spin coating, spray coating, and cast coating; the carrier can be a continuous steel strip, polyester film, copper foil, aluminum foil, glass, or a mirror steel plate.
[0041] In other embodiments of the present invention, a fluorinated polyamide ester adhesive is coated on a carrier, and after a pre-baking and curing stage is performed and the adhesive film is cured into a semi-dry film, the semi-dry film is peeled off the carrier and supported by a hollow frame. For example, the edge of the film is fixed by using needle plates, chain clamps and other equipment used in the existing polyimide film production, and the film is supported and placed in a high-temperature environment to realize the imidization process. This process allows volatiles to escape to both sides of the film, thereby avoiding the situation where the solvent evaporates on one side and causes uneven pores on both sides.
[0042] The above-mentioned film preparation process matches the conventional polyimide film production process. There is no need to add new processes and new equipment on the basis of the conventional polyimide film production process and equipment. The film preparation process is efficient and low-cost, which is conducive to the rapid realization of large-scale industrial production of microporous fluorinated polyimide film materials.
[0043] Preferably, the method for preparing the microporous fluorinated polyimide film material provided by the present invention comprises the following steps:
[0044] S1) reacting a dianhydride having a structure of formula a with a diamine having a structure of formula b to obtain a polyamic acid;
[0045] H2N-Ar2-NH2 formula b;
[0046] S2) reacting the monohydroxy compound with the polyamic acid obtained in step S1) to obtain a fluorinated polyamide ester; the monohydroxy compound is selected from C2 to C 60 Alkyl alcohol alkanoate and a monohydroxy-terminated poly(dimethylsiloxane) having the structure of formula C;
[0047]
[0048] S3) performing an imidization reaction on the fluorinated polyamide ester obtained in step S2) to obtain a microporous fluorinated polyimide film material.
[0049] The reaction formula of the preparation method of the above-mentioned microporous fluorinated polyimide film material is as follows:
[0050]
[0051] Specifically, the present invention firstly conducts a polycondensation reaction of a dianhydride having a structure of formula a and a diamine having a structure of formula b in a solvent to obtain a polyamic acid. The temperature of the polycondensation reaction of the present invention is -5°C to 50°C, preferably 0°C to 25°C, and the time of the polycondensation reaction is 15h to 17h, preferably 16h. The solvent of the present invention includes but is not limited to N,N′-dimethylformamide (DMF), N,N′-dimethylacetamide (DMAc), N-methylpyrrolidone, dimethyl sulfoxide (DMSO), tetrahydrofuran / methanol mixture (THF / MeOH), etc.
[0052] After obtaining the polyamic acid, the present invention reacts the monohydroxy compound with the polyamic acid obtained in step S1) in the presence of a catalyst to obtain a fluorinated polyamide ester; the monohydroxy compound is selected from C2 to C 60 Alkyl alcohol ester and monohydroxyl-terminated poly (dimethylsiloxane) having a structure of formula C. The monohydroxy compound of the present invention is selected from two types, one of which is C2-C 60 Alkyl alcohol esters, including C2~C60 Fatty straight chain alkanoic acid ester alkyl alcohol and C2~C 60 Fatty branched chain alkanoic acid ester alkyl alcohol, preferably C4~C 15 Alkyl alcohol ester, preferably C2-C 60 Alkyl alkanoate; In certain embodiments of the present invention, the C2 to C 60 The alkanoate alkyl alcohol is selected from at least one of 6-hydroxycaproic acid methyl ester, 8-hydroxyoctanoic acid methyl ester or 6-hydroxycaproic acid ethyl ester. The other is a monohydroxy-terminated poly (dimethylsiloxane) having a structure of formula c, wherein R and x in formula c are the same as R and x in the aforementioned formula Ib, and are not repeated here; the reaction temperature is -10°C to 30°C, preferably -5°C to 15°C. The catalyst of the present invention includes but is not limited to the following compounds: at least one of trimethylamine, triethylamine, tripropylamine, tributylamine, N,N'-dimethylalkylamine, pyridine, alkylpyridine or benzylpyridine.
[0053] The monohydroxyl-terminated poly(dimethylsiloxane) in step S2) of the present invention accounts for 5% to 30% of the total amount of the monohydroxyl compound, preferably 12% to 18%. The grafting rate on the molecular chain of the polymer intermediate with alkanoate alkyl and poly(dimethylsiloxane)-based side chains synthesized by the present invention is 1% to 100%, and most preferably 80% to 100%. The percentage of poly(dimethylsiloxane) groups in the amount of branched substances is 5% to 30%, and the preferred percentage is 9% to 13%. The present invention adopts a chemical reaction process known in the industry to synthesize a polymer intermediate with alkanoate alkyl and poly(dimethylsiloxane)-based side chains.
[0054] After obtaining the fluorinated polyamide ester in step S2), the fluorinated polyamide ester obtained in step S2) is subjected to imidization reaction to obtain a microporous fluorinated polyimide film material. The imidization reaction of the fluorinated polyamide ester obtained in step S2) is the same as the above, and will not be repeated.
[0055] The preparation method provided by the present invention is to finally obtain a multi-microporous polyimide film material. By optimizing the chemical reaction sequence, a dianhydride and a diamine are reacted to generate a polyamic acid glue solution, and then an alkanoate alkyl alcohol and a monohydroxyl-terminated poly (dimethylsiloxane) are added to the polyamic acid glue solution, and react with a carboxyl group under the action of a catalyst to uniformly distribute the material on the main chain of the polymer molecule in the form of a chemical bond, thereby obtaining a polymer intermediate of a multi-porous fluorinated polyimide film. On the one hand, such compounds can effectively promote phase separation inside the system during the amidation stage of the film-forming process, forming a pore structure with uniform size and distribution, thereby solving the problem that it is difficult for fluorinated polyimide to form intrinsic micropores; on the other hand, the problem of lower activity and low polymerization degree caused by monomers with large side groups can be avoided. Finally, a porous fluorinated polyimide film with good mechanical properties is obtained through the membrane making process. The chemical reaction pore-inducing method is more conducive to the formation of intrinsic pores of uniform size and distribution inside the film, and it also effectively avoids the deterioration of the film by some physical processes. The heat resistance and dielectric properties of the obtained film are very excellent, and the film also has lower water absorption and excellent chemical stability, and has broad application prospects in aerospace, integrated circuits and new energy fields.
[0056] In the preparation process of porous polyimide film, the best pore-forming method is to naturally generate pores as the chemical reaction proceeds. This pore-forming method does not affect the regularity of the molecular chain of the polymer and does not cause any damage to the macroscopic and microscopic structures of the material. The pores are gradually formed during the chemical reaction. The size and structure of the pores are more in line with the performance of the material itself, and the pore structure can be adjusted in a targeted manner by adjusting the proportion of the pore-forming substance. Although this pore-forming method has many advantages, it is very difficult to implement the pore-forming method even in ordinary polymer materials. The difficulty of implementing it in polyimide, a material with strong rigidity and higher temperature resistance, can be imagined. In response to this technical problem, the present invention provides a microporous fluorinated polyimide film material and a preparation method thereof. Based on many years of research and accumulation on the structure and performance of polyimide materials, combined with the characteristics of fluorinated polyimide itself, the chemical activity and physical properties of a variety of intended compounds are investigated and analyzed, and based on a large number of experiments, it is found that C2~C 60 Alkyl alcohol esters and poly (dimethylsiloxane) monohydroxyl end-capping compounds have the best effect on the gradual pore formation of microporous fluorinated polyimide film materials along with chemical reactions. The present invention uses special grafting groups to gradually form pores along with chemical reactions, which not only solves the problem of deterioration of the comprehensive performance of the film caused by other pore formation methods, but more importantly, this pore formation mechanism can be realized using traditional polyimide film production equipment and production processes, the film preparation technology is more mature, the production cost is lower, the continuous efficiency of the preparation process is higher, and it is easier to realize the continuous production of porous polyimide films. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is a SEM scanning cross-sectional morphology image of the porous fluorinated polyimide film prepared in Example 1;
[0058] Figure 2 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Example 2;
[0059] Figure 3 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Example 3;
[0060] Figure 4 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Example 4;
[0061] Figure 5 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Example 5;
[0062] Figure 6 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Example 6;
[0063] Figure 7 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Comparative Example 1;
[0064] Figure 8 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Comparative Example 2;
[0065] Fig. 9 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Comparative Example 3. DETAILED DESCRIPTION
[0066] The present invention discloses a microporous fluorinated polyimide film material and a preparation method thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0067] The test instruments, test conditions and methods for the performance test of the samples in the present invention are as follows:
[0068] 1. Micromorphology characterization: XL30 (FEI Company, USA) field emission environmental scanning electron microscope (SEM) was used to observe the micromorphology of the microporous polyimide film after gold spraying.
[0069] 2. Heat resistance: TGA-2 thermogravimetric analyzer (TGA), PerkinElmer, USA, heating rate 10°C / min, nitrogen atmosphere.
[0070] 3. Glass transition temperature: static thermomechanical analyzer (TMA Q400), the test atmosphere is nitrogen, the heating rate is 5°C / min, and the temperature range is 40°C to 400°C.
[0071] 4. Mechanical properties: Mechanical properties testing machine (Instron-1121), tensile rate 5mm / min, sample strip size 50mm×10mm, test results are the average of 10 test sample strips;
[0072] 5. Porosity test: The present invention adopts density calculation method. Use a mold knife to cut the porous film into 20mm×20mm square samples, weigh the film mass and measure its thickness, and calculate the density of the sample. The density of polyimide is 1.4g / cm 3 The porosity is calculated by the following formula:
[0073]
[0074] Where ρ1 is the sample density calculated based on mass and volume, and ρ0 is the polyimide density.
[0075] The molecular weight of the monohydroxy-terminated poly(dimethylsiloxane) used in the specific embodiment of the present invention is in the range of 600 to 6000.
[0076] The present invention will be further described below in conjunction with embodiments:
[0077] Example 1
[0078] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a cold bath with the cold bath temperature set to -3°C. 16.012g of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl and 100mL of N,N'-dimethylacetamide (DMAc) were added to the reaction bottle. Mechanical stirring was turned on. After the solid was completely dissolved, 14.711g of biphenyltetracarboxylic dianhydride (BPDA) was added to the reaction bottle. The temperature of the reaction solution was controlled to be ≤25°C. After the addition was completed, the cold bath was closed and the reaction was continued at room temperature for 16h to obtain a light yellow viscous glue solution.
[0079] Turn on the cold bath and set the temperature to -3°C. After the temperature of the above-mentioned glue solution reaches the set temperature, add 13.156g of methyl 6-hydroxyhexanoate and 6.044g of poly(dimethylsiloxane) monohydroxyl-terminated therein, mix evenly with the glue solution, dilute 10.12g of triethylamine with 30mL of DMAc and slowly add it dropwise to the reaction solution. After the addition is completed, turn off the cold bath and return to room temperature to continue the reaction for 8h to obtain a light yellow viscous glue solution.
[0080] The above adhesive solution is filtered and defoamed, then coated on a glass plate, placed in a 100°C film drying oven and baked for 1 hour to completely solidify the adhesive film, and then the adhesive film is peeled off from the glass plate, and the peeled adhesive film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 350°C and kept for 0.5 hour to obtain a fluorinated polyimide porous film.
[0081] The microporous morphology of the prepared polyimide film is shown in Figure 1 As shown, Figure 1 This is a SEM scanning cross-sectional morphology of the porous fluorinated polyimide film prepared in Example 1. The relevant performance characterization of the film is shown in Appendix 1.
[0082] Example 2
[0083] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a cold bath with the cold bath temperature set to -3°C. 16.012g of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl and 100mL of N,N'-dimethylacetamide (DMAc) were added to the reaction bottle. Mechanical stirring was turned on. After the solid was completely dissolved, 10.906g of pyromellitic dianhydride (PMDA) was added to the reaction bottle. The temperature of the reaction solution was controlled to be ≤25°C. After the addition was completed, the cold bath was closed and the reaction was continued at room temperature for 16h to obtain a light yellow viscous glue solution.
[0084] Turn on the cold bath and set the temperature to -3°C. After the temperature of the above-mentioned glue solution reaches the set temperature, add 13.156g of methyl 6-hydroxyhexanoate and 6.044g of poly(dimethylsiloxane) monohydroxyl-terminated therein, mix evenly with the glue solution, dilute 10.12g of triethylamine with 30mL of DMAc and slowly add it dropwise to the reaction solution. After the addition is completed, turn off the cold bath and return to room temperature to continue the reaction for 8h to obtain a light yellow viscous glue solution.
[0085] The above adhesive solution is filtered and defoamed, then coated on a glass plate, placed in a 100°C film drying oven and baked for 1 hour to completely solidify the adhesive film, and then the adhesive film is peeled off from the glass plate, and the peeled adhesive film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 350°C and kept for 0.5 hour to obtain a fluorinated polyimide porous film.
[0086] The microporous morphology of the prepared polyimide film is shown in Figure 2 As shown, Figure 2 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Example 2. The relevant performance characterization of the film is shown in Appendix 1.
[0087] Example 3
[0088] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a cold bath set at -3°C, 16.012g of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl was added to the reaction bottle, 80mL of N,N'-dimethylacetamide (DMAc) was added, mechanical stirring was turned on, and after the solid was completely dissolved, 10.906g of pyromellitic dianhydride (PMDA) was added to the reaction bottle, the temperature of the reaction liquid was controlled to be ≤25°C, the cold bath was closed after the addition was completed, and the reaction was continued at room temperature for 16h to obtain a light yellow viscous glue solution.
[0089] Turn on the cold bath and set the temperature to -3°C. After the temperature of the above-mentioned glue solution reaches the set temperature, add 14.419g of 6-hydroxyhexanoic acid ethyl ester and 6.044g of poly(dimethylsiloxane) monohydroxyl end-capping therein, mix evenly with the glue solution, dilute 10.12g of triethylamine with 28mL of DMAc and slowly add it dropwise to the reaction solution. After the addition is completed, turn off the cold bath and return to room temperature to continue the reaction for 8h to obtain a light yellow viscous glue solution.
[0090] The above adhesive solution is filtered and defoamed, then coated on a glass plate, placed in a 100°C film drying oven and baked for 1 hour to completely solidify the adhesive film, and then the adhesive film is peeled off from the glass plate, and the peeled adhesive film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 350°C and kept for 0.5 hour to obtain a fluorinated polyimide porous film.
[0091] The microporous morphology of the prepared polyimide film is shown in Figure 3 As shown, Figure 3 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Example 3. The relevant performance characterization of the film is shown in Appendix 1.
[0092] Example 4
[0093] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a cold bath set at -3°C, 10.012g of 4,4'-diaminodiphenyl ether (ODA) and 100mL of N-methyl-2-pyrrolidone (NMP) acetamide (DMAc) were added to the reaction bottle, and mechanical stirring was turned on. After the solid was completely dissolved, 22.212g of hexafluorodianhydride (6FDA) was added to the reaction bottle. The temperature of the reaction liquid was controlled to be ≤25°C. After the addition was completed, the cold bath was closed and the reaction was continued at room temperature for 16h to obtain a light yellow viscous glue solution.
[0094] Turn on the cold bath and set the temperature to -3°C. After the temperature of the above-mentioned glue solution reaches the set temperature, add 15.682g of 8-hydroxyoctanoic acid methyl ester and 6.044g of poly(dimethylsiloxane) monohydroxyl end-capping thereto. After mixing evenly with the glue solution, dilute 10.12g of triethylamine with 29mL of NMP and slowly add it dropwise to the reaction solution. After the addition is completed, turn off the cold bath and return to room temperature to continue the reaction for 8h to obtain a light yellow viscous glue solution.
[0095] The above adhesive solution is filtered and defoamed, then coated on a glass plate, placed in a 100°C film drying oven and baked for 1 hour to completely solidify the adhesive film, and then the adhesive film is peeled off from the glass plate, and the peeled adhesive film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 350°C and kept for 0.5 hour to obtain a fluorinated polyimide porous film.
[0096] The microporous morphology of the prepared polyimide film is shown in Figure 4 As shown, Figure 4 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Example 4. The relevant performance characterization of the film is shown in Appendix 1.
[0097] Example 5
[0098] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a cold bath set at -3°C, 14.617g of 1,3,3-triphenyl diether diamine (1,3,3-APB) and 100mL of N-methyl-2-pyrrolidone (NMP) acetamide (DMAc) were added to the reaction bottle, mechanical stirring was turned on, and after the solid was completely dissolved, 22.212g of hexafluorodianhydride (6FDA) was added to the reaction bottle, the temperature of the reaction liquid was controlled to be ≤25°C, the cold bath was closed after the addition was completed, and the reaction was continued at room temperature for 16h to obtain a light yellow viscous glue solution.
[0099] Turn on the cold bath and set the temperature to -3°C. After the temperature of the above-mentioned glue solution reaches the set temperature, add 15.682g of 8-hydroxyoctanoic acid methyl ester and 6.044g of poly(dimethylsiloxane) monohydroxyl end-capping thereto. After mixing evenly with the glue solution, dilute 10.12g of triethylamine with 47mL of NMP and slowly add it dropwise to the reaction solution. After the addition is completed, turn off the cold bath and return to room temperature to continue the reaction for 8h to obtain a light yellow viscous glue solution.
[0100] The above adhesive solution is filtered and defoamed, then coated on a glass plate, placed in a 100°C film drying oven and baked for 1 hour to completely solidify the adhesive film, and then the adhesive film is peeled off from the glass plate, and the peeled adhesive film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 350°C and kept for 0.5 hour to obtain a fluorinated polyimide porous film.
[0101] The microporous morphology of the prepared polyimide film is shown in Figure 5 As shown, Figure 5 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Example 5. The relevant performance characterization of the film is shown in Appendix 1.
[0102] Example 6
[0103] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a cold bath set at -3°C, 16.012g of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl and 100mL of N-methyl-2-pyrrolidone (NMP) acetamide (DMAc) were added to the reaction bottle, and mechanical stirring was turned on. After the solid was completely dissolved, 11.106g of hexafluorodianhydride (6FDA) and 7.356g of BPDA were added to the reaction bottle. The temperature of the reaction liquid was controlled to be ≤25°C. After the addition was completed, the cold bath was closed and the reaction was continued at room temperature for 16h to obtain a light yellow viscous glue.
[0104] Turn on the cold bath and set the temperature to -3°C. After the temperature of the above-mentioned glue solution reaches the set temperature, add 14.419g of 6-hydroxyhexanoic acid ethyl ester and 6.044g of poly(dimethylsiloxane) monohydroxyl end-capping thereto. After mixing evenly with the glue solution, dilute 10.12g of triethylamine with 37mL of NMP and slowly add it dropwise to the reaction solution. After the addition is completed, turn off the cold bath and return to room temperature to continue the reaction for 8h to obtain a colorless viscous glue solution.
[0105] The above adhesive solution is filtered and defoamed, then coated on a glass plate, placed in a 100°C film drying oven and baked for 1 hour to completely solidify the adhesive film, and then the adhesive film is peeled off from the glass plate, and the peeled adhesive film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 350°C and kept for 0.5 hour to obtain a fluorinated polyimide porous film.
[0106] The microporous morphology of the prepared polyimide film is shown in Figure 6 As shown, Figure 6 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Example 6. The relevant performance characterization of the film is shown in Appendix 1.
[0107] Comparative Example 1
[0108] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a cold bath with the cold bath temperature set to -3°C. 16.012g of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl and 100mL of N,N'-dimethylacetamide (DMAc) were added to the reaction bottle. Mechanical stirring was turned on. After the solid was completely dissolved, 10.906g of pyromellitic dianhydride (PMDA) was added to the reaction bottle. The temperature of the reaction liquid was controlled to be ≤25°C. After the addition was completed, the cold bath was closed and the reaction was continued at room temperature for 16h to obtain a light yellow viscous glue solution.
[0109] Turn on the cold bath and set the temperature to -3°C. After the temperature of the above-mentioned glue solution reaches the set temperature, add 14.618g of methyl 6-hydroxyhexanoate thereto and mix it evenly with the glue solution. Then, dilute 10.12g of triethylamine with 30mL of DMAc and slowly add it dropwise to the reaction solution. After the addition is completed, turn off the cold bath and return to room temperature to continue the reaction for 8h to obtain a light yellow viscous glue solution.
[0110] The above adhesive solution is filtered and defoamed, then coated on a glass plate, placed in a 100°C film drying oven and baked for 1 hour to completely solidify the adhesive film, and then the adhesive film is peeled off from the glass plate, and the peeled adhesive film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 350°C and kept for 0.5 hour to obtain a fluorinated polyimide porous film.
[0111] The microporous morphology of the prepared polyimide film is shown in Figure 7 As shown, Figure 7 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Comparative Example 1. The relevant performance characterization of the film is shown in Appendix 1.
[0112] Comparative Example 2
[0113] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a cold bath with the cold bath temperature set to -3°C. 16.012g of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl and 100mL of N,N'-dimethylacetamide (DMAc) were added to the reaction bottle. Mechanical stirring was turned on. After the solid was completely dissolved, 10.906g of pyromellitic dianhydride (PMDA) was added to the reaction bottle. The temperature of the reaction liquid was controlled to be ≤25°C. After the addition was completed, the cold bath was closed and the reaction was continued at room temperature for 16h to obtain a light yellow viscous glue solution.
[0114] Turn on the cold bath and set the temperature to -3°C. After the temperature of the above-mentioned glue solution reaches the set temperature, add 17.424g of 8-hydroxyoctanoic acid methyl ester and mix it evenly with the glue solution. Then, dilute 10.12g of triethylamine with 30mL of DMAc and slowly add it dropwise to the reaction solution. After the addition is completed, turn off the cold bath and return to room temperature to continue the reaction for 8h to obtain a light yellow viscous glue solution.
[0115] The above adhesive solution is filtered and defoamed, then coated on a glass plate, placed in a 100°C film drying oven and baked for 1 hour to completely solidify the adhesive film, and then the adhesive film is peeled off from the glass plate, and the peeled adhesive film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 350°C and kept for 0.5 hour to obtain a fluorinated polyimide porous film.
[0116] The microporous morphology of the prepared polyimide film is shown in Figure 8 As shown, Figure 8 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Comparative Example 2. The relevant performance characterization of the film is shown in Appendix 1.
[0117] Comparative Example 3
[0118] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a cold bath with the cold bath temperature set to -3°C. 16.012g of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl and 100mL of N,N'-dimethylacetamide (DMAc) were added to the reaction bottle. Mechanical stirring was turned on. After the solid was completely dissolved, 10.906g of pyromellitic dianhydride (PMDA) was added to the reaction bottle. The temperature of the reaction liquid was controlled to be ≤25°C. After the addition was completed, the cold bath was closed and the reaction was continued at room temperature for 16h to obtain a light yellow viscous glue solution.
[0119] Turn on the cold bath and set the temperature to -3°C. After the temperature of the above-mentioned glue solution reaches the set temperature, add 7.309g of methyl 6-hydroxyhexanoate and 30.217g of poly(dimethylsiloxane) monohydroxyl end-capping therein, mix evenly with the glue solution, dilute 10.12g of triethylamine with 30mL of DMAc and slowly add it dropwise to the reaction solution. After the addition is completed, turn off the cold bath and return to room temperature to continue the reaction for 8h to obtain a light yellow viscous glue solution.
[0120] The above adhesive solution is filtered and defoamed, then coated on a glass plate, placed in a 100°C film drying oven and baked for 1 hour to completely solidify the adhesive film, and then the adhesive film is peeled off from the glass plate, and the peeled adhesive film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 350°C and kept for 0.5 hour to obtain a fluorinated polyimide porous film.
[0121] The microporous morphology of the prepared polyimide film is shown in Fig. 9 As shown, Fig. 9 This is a SEM scanning morphology of the micropores of the porous fluorinated polyimide film prepared in Comparative Example 3. The relevant performance characterization of the film is shown in Appendix 1.
[0122] Table 1
[0123]
[0124]
[0125] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A microporous fluorinated polyimide film material, characterized in that: It is obtained by imidization reaction of fluorinated polyamide ester having a structure of formula I; Wherein, said z≥1000; Ar1 and Ar2 are independently selected from substituted or unsubstituted fluorine-containing aromatic groups, substituted or unsubstituted fluorine-containing heteroaromatic groups, substituted or unsubstituted fluorine-containing aliphatic groups, substituted or unsubstituted aromatic groups, substituted or unsubstituted heteroaromatic groups, substituted or unsubstituted aliphatic groups; The M1 and M2 are independently selected from C2 to C 60 Alkanoate alkyl or poly (dimethylsiloxane) group, and the M1 and M2 are the same or different; The structural unit of the fluorine-containing polyamide ester includes a structural unit containing at least one of Ar1 and Ar2 and a structural unit containing no fluorine.
2. The microporous fluorinated polyimide film material according to claim 1, characterized in that: In the fluorinated polyamide ester, the molar ratio of at least one fluorinated structural unit in Ar1 and Ar2 to all structural units is 1% to 100%.
3. The microporous fluorinated polyimide film material according to claim 1, characterized in that: The M1 and M2 are independently selected from C2 to C 60 Alkanoate alkyl or poly(dimethylsiloxane) group having the structure of Formula Ib; Wherein, n≥1, m≥1; x≥1; The R is a fatty chain.
4. The microporous fluorinated polyimide film material according to claim 1, characterized in that: The fluorine-containing polyamide ester having the structure of formula I has a poly(dimethylsiloxane) group, and the molar amount of the poly(dimethylsiloxane) group accounts for 5% to 30% of the total molar amount of M1 and M2.
5. The microporous fluorinated polyimide film material according to claim 1, characterized in that: Ar1 has one or more structures of formula Ar1-a to formula Ar1-i; Ar2 has one or more structures of formula Ar2-a to formula Ar2-h; Wherein, R1 and R2 are independently selected from H, F or trifluoromethyl; The R 1 and R 2 One independently selected from the groups represented by the structures of Formula 1 to Formula 9; The X is selected from hydrogen, alkyl, cycloalkyl, aryl, fluoroalkyl, hydroxyl, alkoxy, phenoxy, cyano, nitro, amino, acetylamino, ester, acyl, halide or carboxyl; The y is independently an integer of 1-4.
6. The microporous fluorinated polyimide film material according to claim 1, characterized in that: The microporous fluorinated polyimide film material has a structure of formula II; 7. The method for preparing the microporous fluorinated polyimide film material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The fluorine-containing polyamide ester is subjected to imidization reaction to obtain a microporous fluorine-containing polyimide film material.
8. The method for preparing a microporous fluorinated polyimide film material according to claim 7, characterized in that: The specific steps include: S1) reacting a dianhydride having a structure of formula a with a diamine having a structure of formula b to obtain a polyamic acid; H2N-Ar2-NH2 formula b; S2) reacting the monohydroxy compound with the polyamic acid obtained in step S1) to obtain a fluorinated polyamide ester; the monohydroxy compound is selected from C2 to C 60 Alkyl alcohol alkanoate and a monohydroxy-terminated poly(dimethylsiloxane) having the structure of formula C; S3) performing an imidization reaction on the fluorinated polyamide ester obtained in step S2) to obtain a microporous fluorinated polyimide film material.
9. The method for preparing a microporous fluorinated polyimide film material according to claim 8, characterized in that: In step S2), the reaction temperature is -10°C to 30°C, and the reaction time is 15h to 17h.
10. The method for preparing a microporous fluorinated polyimide film material according to any one of claims 7 to 9, characterized in that: The temperature of the imidization reaction is 50° C. to 400° C., and the time of the imidization reaction is 0.3 h to 30 h.
Citation Information
Patent Citations
Preparation method of temperature responsive composite microporous membrane
CN105552276A
Varnish for optical alignment film and liquid crystal display device
CN112764274A
Polyimide film with siloxane grafted on side chain
CN114736409A
Polymer, preparation method thereof, composition and polyimide film
CN116751364A
Photosensitive polyamic acid ester resin, resin composition and preparation method and application of photosensitive polyamic acid ester resin
CN117384378A